Towards social cohesion: understanding local migration governance's barriers in global south smart cities - Alves Palacios, Rosiane; Mezzomo Luciano, Edimara; Viale Pereira, Gabriela (Conference on Digital Government Research, 2025)
Smart cities (SC) are becoming increasingly popular around the world. Within the scope of SC studies is governance, which is directly related to the success of planned actions. Refugee migration is currently a challenge all over the world. But at the local level (cities) it can be better examined. The local migration governance network is one way for welcoming and integrating refugees in cities. However, there are barriers that can influence smart governance as well as migration governance. It is important that cities can be more inclusive and effective in welcoming migrants and refugees by promoting social cohesion. This study aimed to identify barriers of local migration governance in two smart cities in order to reflect on the possibility of increasing social cohesion for immigrants and refugees. A multiple case study was carried out on the local migration governance networks of two smart cities in the Global South: Porto Alegre-BRA and Cape Town-ZA. Twenty-five interviews were collected with migration experts and local migration governance actors, nine documents were analyzed, and observations were made in both cities. The data was analyzed through content analysis. The results of the research pointed to sixteen structural, social and political barriers. Social cohesion can be built through public policies that take diversity into account and where, once integrated, refugees can truly feel that they belong to the community. We propose a frame that summarize the actions that can promote social cohesion for immigrants and refugees in smart cities. We based the actions proposed on the barriers and the possibilities of interventions.